EVALUASI LITTER SIZE DARI PEJANTAN DENGAN INDUK BERBEDA PADA USAHA PETERNAKAN BABI SKALA KECIL DI DESA BUAHAN PAYANGAN - I. G., SURANJAYA; SUKANATA, I. W.; OKA, A. A. (Majalah Ilmiah Peternakan, 2023)
This study aims to evaluate litter size of different ages males with different parent parity in smallholder pig far- ming, used 3 males of different ages (P1, P2, P3) and 18 sows of parity 1 – 4 (I1, I2, I3 and I4) with a 3 x 4 factorial RAL experimental design and unequal number of replications. The variables observed were litter size, weaning litter size, mortality and percentage of weaning litter size. Data were analyzed using a analyse of variant with the general linear model procedure. The results showed that the average litter size based on males P1, P2, P3 was 8.38; 9.13 and 10.38 (P>0.05) and based on parental parity I1, I2, I3 and I4 respectively 8.00; 8.83; 9.66 and 10.66 (P<0.05). For weaning litter size, respectively 5.75; 7.50 and 8.87 (P<0.05) and from parent parity was 6.17; 6.67; 8.17 and 8.50 (P<0.05), while the mortality respectively was 31.82%; 17.62% and 12.39% (P>0.05) and from parent parity respec- tively 23.54%; 23.21%; 15.74%; and 19.94% (P>0.05). Weaning litter size percentage of each male was 68.17; 82.50; 87.61 (P>0.05) and from parental parity 76.63; 76.78; 84.26 and 80.05 (P>0.05). Older males and fourth parity of parent produced better litter size, weaning litter size and weaning litter percentage with lower mortality. There was no interaction between the use of males of different ages and parents of different parity on the observed variables.